Six NSCL/P Loci Show Associations With Normal-Range Craniofacial Variation - Indencleef, Karlijne; Roosenboom, Jasmien; Hoskens, Hanne; White, Julie D.; Shriver, Mark D.; Richmond, Stephen; Peeters, Hilde; Feingold, Eleanor; Marazita, Mary L.; Shaffer, John R.; Weinberg, Seth M.; Hens, Greet; et al. (Frontiers in Genetics, 2018)
Objectives Orofacial clefting is one of the most prevalent craniofacial malformations. Previous research has demonstrated that unaffected relatives of patients with non-syndromic cleft lip with/without cleft palate (NSCL/P) show distinctive facial features, which can be an expression of underlying NSCL/P susceptibility genes. These results support the hypothesis that genes involved in the occurrence of a cleft also play a role in normal craniofacial development. In this study, we investigated the influence of genetic variants associated with NSCL/P on normal-range variation in facial shape. Methods A literature review of genome wide association studies (GWAS) investigating the genetic etiology of NSCL/P was performed, resulting in a list of 74 single nucleotide polymorphisms (SNPs) located in 36 genetic loci. Genotype data were available for 64 of these selected SNPs in three datasets with a combined sample size of 7,418 participants of European ancestry, whose 3D facial images were also available. The effect of each SNP was tested using a multivariate canonical correlation analysis (CCA) against 63 hierarchically-constructed facial segments in each of the three datasets and meta-analyzed. This allowed for the investigation of associations between SNPs known to be involved in NSCL/P and normal-range facial shape variations in a global-to-local perspective, without preselecting specific facial shape features or characteristics. Results Six NSCL/P SNPs showed significant associations with variation in normal-range facial morphology. rs6740960 showed significant effects in the chin area (p=3.71x10-28). This SNP lies in a non-coding area. Another SNP, rs227731 near the NOG gene, showed a significant effect in the philtrum area (p=1.96x10-16). Three SNPs showed significant effects on the shape of the nose. rs742071 (p=8.71x10-14), rs34246903 (p=6.87x10-12) and rs10512248 (p=8.4x10-9). Respectively, these SNPs are annotated to PAX7, MSX1 and PTCH1. Finally, rs7590268, an intron variant of THADA, showed an effect in the shape of the supraorbital ridge (p=3.84x10-7). Conclusions This study provides additional evidence NSCL/P-associated genetic variants influence normal-range craniofacial morphology, with significant effects observed for the chin, the nose, the supraorbital ridges and the philtrum area.